A STUDY IN THE BIOLOGICAL TREATMENT OF THE DOMESTIC AND LOCAL INDUSTRIAL SEWAGES - Mirza , Sardar (The Iraqi Journal of Veterinary Medicine, 1990)
Total sewage of the middle-sized town in our country having different local industries of various complexity may contain a large scale of harmful materials for the environmnt and aquatic life. Waste waters derived out from such a town is treated bfore theu take their ways to the streams and rivers. High percentage of organic wastes was removed from the total town waste waters by the microbial activity of activated sludge. Organisms of activated sludge were adapted in such a way to help in these waste removals. Some selected bacterial species were organized for this purpose. The time and the dilution factors were counted for, to give the best results. The method of chemical oxygeen demand COD was used as a measurement for the degree of purification. It is possible to get even better results by the treatment of the final outflow and more adaptation of the bacterial microflora of activated sludge.